The phenomenon of medieval “easter eggs”: types of artifacts, probable ways of their distribution and functions (based on finds from the territory of Belarus in the European context) - Makouskaya, Viktoryia (Folia Praehistorica Posnaniensia, 2024)
The paper is devoted to such type of artifacts as “Easter eggs”, also known in the scientific literature as egg-shaped rattles or pisanki. The study considers such problems as the provenance of these artifacts and their function and meaning. In addition to glazed ceramic egg-shaped rattles, imitation eggs made of other materials are considered as part of the same phenomenon. The artifacts from the territory of Belarus were mostly found in towns and do not have a specific context. The majority of the finds dates back to a later period in comparison with the neighboring territories of Old Rus’. The distribution and occurrence of egg-shaped objects in towns and villages corresponded to the period of active spread of Christianity and church building, which indicates that it will be more appropriate to consider these finds in the context of Christianity.